Military Skill And Training In Soldier’s Bravery (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Malaysian Armed Forces is responsible for producing hundreds of thousands of trained military personnel. This is because the Malaysian Armed Forces has carried out various military exercises to expose the role of its personnel and provide awareness of the importance of military service in the context of national defense and security. Bravery is a leading to matters related to a mentally and physically strong fighting spirit despite facing high risks. Then, bravery is one of the most important qualities that should have among the soldier personnel. The need to manage training efficiently and effectively is a challenge that needs to be managed and addressed properly, systematically and systematically. Technological advances that are constantly changing with the current circulation require a system of training that is effective enough to help the Government produce personnel that are feared by the enemy. The objective of this study is to determine the relationship of the military skill and military training with the soldier bravery among Malaysian Armed Forces in IJED, Port Dickson, KDSI, Lumut Perak and KTU, Alor Setar Kedah. Quantitative research methods of the correlational research design were conducted using questionnaires with 249 respondents from the Malaysian Armed Forces using the Statistical Package for the Social Sciences 25.0 and Smart PLS 3.3.2. The results showed that there is a relationship between the military skill and military training with the soldier bravery. The findings confirmed that military skill and military training does act as an important determinant in the relationship of soldier’s bravery. The organization should define military skill and military training for training programs and specify components or outcomes to target in order to better understand soldier’s bravery. This study confirmed that the ability of commanding officers to conduct training appropriately military mind elements military skill and military training has increased their soldier’s bravery in operations.